Evaluating inter-aural hearing preservation in bilateral paediatric cochlear implantation. (2nd November 2018) - Jones, Huw A. S.; Powell, Harry R. F.; Hall, Andy; Lavy, Jeremy; Shaida, Azhar; Saeed, Shakeel; Khalil, Sherif
Abstract : Objective: To examine inter-aural hearing preservation results in children undergoing simultaneous bilateral cochlear implantation (CI). Methods: Retrospective case review in tertiary referral centre. All children undergoing simultaneous bilateral CI between January 2013 and June 2014 (18 months). Patients eligible for inclusion in the study had pre-operative hearing thresholds of <90 dB at 250 Hz and ≥100 dB at 500 Hz. Patients with anatomical cochlear anomalies or missing data were excluded. Seven patients were included, 1 male, 6 female, mean age of 12 years 11 months at the time of surgery. All patients had simultaneous bilateral cochlear implant surgery, using the same implant and technique. All patients had pre- and post-operative unaided pure tone audiometry. Inter-aural hearing preservation results were compared in each patient. Results: The achieved hearing preservation for 14 ears was complete in 5, partial in 7, and minimal in 2. Measurable hearing preservation was achieved in 86% overall. Inter-aural analysis revealed that only 2 (subjects 1 and 4) of the 7 patients had preservation results within the same preservation group (complete/partial/minimal). The mean inter-aural preservation difference was 30.7% with a range from 12.4% to 65.2%. Conclusions: Several factors and techniques have already been identified in the wider literature to explain differences in hearing preservation results in CI. However, despite controlling for known factors, we demonstrate variable inter-aural results. This suggests that there may be more factors beyond the surgeon's control influencing our ability to provide consistent results.